A Comment on "Influence Motives in Social Signaling: Evidence from COVID-19 Vaccinations in Germany" - Jason Collins; Amanda Baptista Denham; Zhuoran Du; David Waller (Institute for Replication (I4R), 2024)
Esguerra, Vollmer and Wimmer (2023) examined respondents' desire to influence other people's choices via their own behaviour. They conducted a field study on German residents' registration for the COVID-19 vaccination, where 1,401 "Senders" made their registration decision, which could then be shared with a peer before or after that peer's decision, providing an understanding of motives and social pressure on decisions. The authors found that individual influence motives increase a participant's likelihood to register for vaccination, but social pressure effects do not alter it. We reproduced the results using the original code and data. We tested the robustness of the primary analysis by (i) using a logistic regression model, (ii) limiting the analysis to participants who inform their partner of their decision, and (iii) changing the criteria by which participants are recorded as "verified registered". We found that these tests did not materially change the effect size estimates or the conclusions to be drawn from the analysis. We also tested the authors' sub-analysis by the level of trust in the vaccine. We found that an alternative cutoff for the high-trust group did not materially change the result.
Keywords: 330